Control of bacterial contamination in microalgae cultures integrated with wastewater treatment by applying feast and famine conditions. Issue 5 (October 2022) - Di Caprio, Fabrizio; Proietti Tocca, Giacomo; Stoller, Marco; Pagnanelli, Francesca; Altimari, Pietro
Abstract: The integration of microalgae production with wastewater treatment can significantly increase economic and environmental sustainability of the treatment process and of the microalgal biomass production. However, a major bottleneck of this strategy is the control of contamination by heterotrophic bacteria, which compete with microalgae for the organic substrate and can negatively affect the quality of the produced biomass. Here, a strategy to control bacterial contamination is proposed, whereby a first batch phase with the medium replete in the organic substrate (feast) is followed by a second batch phase without the organic substrate (famine). Permeates from microfiltration and ultrafiltration of cheese whey were used as sources of organic substrates, with different C/N. Biomass production and pollutant removal were analyzed, and the growth kinetics of microalgae and bacteria were characterized and modeled to determine the specific growth rate (µmax ) during the feast phase and the decay rate ( k D ) during the famine phase. Bacteria had µmax (0.16 h −1 ) about two folds higher than microalgae (0.07 h −1 ), however, bacteria lysed in larger fraction during the famine phase, allowing to reduce contamination. A remarkable finding was that, for both microalgae and bacteria, only a cell subpopulation experienced lysis during the famine phase. The fraction of resistant cells was higher for microalgae and decreased with increasing the C/N ratio in the initial medium, indicating that cell-to-cell heterogeneity for carbon storage is crucial in determining cell resistance. Guidelines are derived to maximize microalgae biomass productivity and pollutant removal while maintaining a prescribed bacterial contamination. Graphical Abstract: ga1 Highlights: Microalgae were cultivated in UF and MF whey permeates in a feast and famine regime. Up to 90% TN, 87% TP and 91% COD were removed from whey permeates. During feast phase bacteria had a µmax (0.16 h −1 ) two folds higher than microalgae. Bacteria contamination was remarkably reduced after 24 h energy starvation (famine). Only a subpopulation of cells lysed during famine phase; it was lower at higher C/N.